Transparency, Information, Sustainability Interaction with Citizens, vs the Fight against Corruption, and Their Role in the Public Sector Auditing. Evidence from Albania - HOXHA, Almida Kafia; MITI, Mirela (Theoretical and Practical Research in Economic Fields, 2025)
Through this study we have attempted to explore the role of transparency and accountability in the functioning of Albania's Supreme Audit Institution (ALSAI/KLSH) and its impact on public trust and the fight against corruption. Drawing on a ten-year analysis of public complaints, audit findings, and transparency initiatives, the research examines the correlation between citizen engagement, audit outcomes, and the level of perceived corruption in Albania. The study utilizes various methodological approaches, including Spearman’s correlation coefficient, to evaluate the effectiveness of KLSH’s transparency practices in fostering public confidence. Results indicate a positive relationship between sustained public interaction with KLSH and a reduction in corruption perceptions, highlighting the importance of institutional transparency and public participation. The study concludes that strengthening the relationship between audit institutions and the public is crucial for ensuring good governance, the rule of law, and preventing corruption. It advocates for further research to enhance the role of Supreme Audit Institutions in promoting accountability and strengthening the rule of law in Albania.